(18)F-glyco-RGD peptides for PET imaging of integrin expression: efficient radiosynthesis by click chemistry and modulation of biodistribution by glycosylation - Maschauer, Simone; Haubner, Roland; Kuwert, Torsten; Prante, Olaf (Molecular Pharmaceutics, 2014)
Glycosylation frequently improves the biokinetics and clearance properties of macromolecules in vivo and could therefore be used for the design of radiopharmaceuticals for positron emission tomography (PET). Recently, we have developed a click chemistry method for (18)F-fluoroglycosylation of alkyne-bearing RGD-peptides targeting the integrin receptor. To investigate whether this strategy could yield an (18)F-labeled RGD glycopeptide with favorable biokinetics, we generated a series of new RGD glycopeptides, varying the 6-fluoroglycosyl residue from monosaccharide to disaccharide units, which provided the glucosyl ([(19)F]6Glc-RGD, 4b), galactosyl ([(19)F]Gal-RGD, 4c), maltosyl ([(19)F]Mlt-RGD, 4e), and cellobiosyl ([(19)F]Cel-RGD, 4f) conjugated peptides in high yields and purities of >97%. All of these RGD glycopeptides showed high affinity to ?v?3 (11-55 nM), ?v?5 (6-14 nM), and to ?v?3-positive U87MG cells (90-395 nM). (18)F-labeling of the various carbohydrate precursors (1a-f) using cryptate-assisted reaction conditions (CH3CN, 85 °C, 10 min) gave (18)F-labeled glycosyl azides in radiochemical yields (RCYs) of up to 84% ([(18)F]2b). The deacetylation and subsequent click reaction with the alkyne-bearing cyclic RGD peptide proceeded in one-pot reactions with RCYs as high as 81% in 15-20 min at 60 °C, using a minimal amount of peptide precursor (100 nmol). Optimization of the radiosynthesis strategy gave a decay-uncorrected RCY of 16-24% after 70-75 min (based on [(18)F]fluoride). Due to their high-yield radiosyntheses, the glycopeptides [(18)F]6Glc-RGD and [(18)F]Mlt-RGD were chosen for comparative biodistribution studies and dynamic small-animal PET imaging using U87MG tumor-bearing nude mice. [(18)F]6Glc-RGD and [(18)F]Mlt-RGD showed significantly decreased liver and kidney uptake by PET relative to the 2-[(18)F]fluoroglucosyl analog [(18)F]2Glc-RGD, and showed specific tumor uptake in vivo. Notably, [(18)F]Mlt-RGD revealed uptake and retention in the U87MG tumor comparable to that of [(18)F]Galacto-RGD. Both [(18)F]6Glc-RGD and [(18)F]Mlt-RGD were obtained by a reliable and easy click chemistry-based procedure, much more rapidly than was [(18)F]Galacto-RGD. Due to its favorable biodistribution and tissue clearance in vivo, [(18)F]Mlt-RGD represents a viable alternative radiotracer for imaging integrin expression in solid tumors by PET.
EVALuna2:13812